Effects of initial radius on the propagation of premixed flame kernals in a turbulent environment - Klein, M.; Chakraborty, N.; Jenkins, Karl W.; Cant, R. S. (American Institute of Physics (AIP), 2006)
The effects of mean curvature on the propagation of turbulent premixed flames have been investigated using three-dimensional direct numerical simulations (DNS) with single step Arrhenius-type chemistry in the thin reaction zones regime. A number of spherical flame kernels with different initial radius have been studied under identical conditions of turbulence and thermochemistry. A statistically planar turbulent back-to-back flame has been simulated as a special case of a spherical kernel in the limit of infinite kernel radius. Statistical analysis in terms of standard and joint probability density functions (pdfs) clearly indicates that the mean curvature of the flame kernel configuration has a major influence on the propagation behavior of the flame. For the planar flame configuration the density-weighted displacement speed is found to be fairly constant throughout the flame brush, in good agreement with previous DNS results. By contrast, for the flame kernel configuration the density-weighted displacement speed is found to vary strongly through the flame brush, changing from values on the order of the corresponding laminar flame speed near the fresh gas side to considerably smaller values near the burned gas side. The joint pdfs of displacement speed and its components with curvature are extensively studied, allowing for an explanation of the observed phenomena in terms of local flame geometry and its interaction with the turbulent flow fiel